The structure of tRNA 5 Lys from Drosophila melanogaster. - Cribbs, D L (1982)
The nucleotide sequence of Drosophila melanogaster tRNA 5 Lys is pGCCCGGAUAm2GCUCAGDCGGDAGAGCA psi psi GGACUsU*UUt6A*A psi CCAAGGm7GDm5CCAGGGTm psi CAm1AGUCCCUGUUCGGGCGCCA. The sU* is probably 5-methylcarboxymethyl-2-thiouridine and t6A* is a mixture of modified derivatives of t6A including t6A itself and a component sensitive to treatment with cyanogen bromide. This tRNA 5 Lys is 95% homologous to the rabbit liver tRNA 5 Lys.